ELEMENTOS DA OBRA FREIREANA E DA TEOLOGIA DA LIBERTAÇÃO NAS DÉCADAS DE 1950 A 1970: UMA ANÁLISE COMBINADA DE SUA GÊNESE E IDENTIDADE - PRADO, Marcio do (2016)
This research aims to analyze the historical, political, social, economic and ideological context in which it appears criticism of Paulo Freire pedagogy and later liberation theology, seeking to find influences of this peculiar context in the genesis of Freire's thought and conceptions of the theologians Rubem Alves and Gustavo Gutierrez, who were the first to publish works on liberation theology, theological current considered genuinely Latin American. It seeks to observe to what extent the pedagogical concepts of Freire may have been taken by Gutierrez Alves and theologians in their works reviewed here. In both thoughts we find the valuation of view of human beings and a praxis that seeks liberation from oppressive systems. Both in Paulo Freire as the fundamentals of this theological current present humanistic principles and elements of the Christian tradition. From the methodological tool of analysis of the Marxist dialectical historical materialism, seeks to identify common themes that are addressed by the authors in their arising works from the 1950s to 1970, pausing to study some of the underlying themes, namely, practice , history , humanism and freedom.